The revolution in freedoms of press and speech from Blackstone to the First Amendment and Fox's Libel Act - Bird, Wendell R. (New York, NY Oxford University Press, 2020)
"This book discusses the revolutionary broadening of concepts of freedom of press and freedom of speech in Great Britain and in America in the late eighteenth century, in the period that produced state declarations of rights and then the First Amendment and Fox's Libel Act. The conventional view of the history of freedoms of press and speech is that the common law since antiquity defined those freedoms narrowly, and that Sir William Blackstone in 1769, and Lord Chief Justice Mansfield in 17770, faithfully summarized the common law in giving a very narrow definition of those freedoms as mere liberty from prior restraint and not liberty from punishment after something was printed or spoken. This book proposes, to the contrary, that Blackstone carefully selected the narrowest definition that had been suggested in popular essays in the prior seventy years, in order to oppose the growing claims for much broader protections of press and speech. Blackstone misdescribed his summary as an accepted common law definition, which in fact did not exist. A year later, Mansfield inserted a similar definition into the common law for the first time, also misdescribing it as a long-accepted definition, and soon misdescribed the unique rules for prosecuting sedition as having an equally ancient pedigree. Blackstone and Mansfield were not declaring the law as it had long been, but were leading a counter-revolution about the breadth of freedoms of press and speech, and cloaking it as a summary of a narrow common law doctrine that in fact was nonexistent. That conflict of revolutionary view and counter-revolutionary view continues today. For over a century, a neo-Blackstonian view has been dominant, or at least very influential, among historians. Contrary to those narrow claims, this book concludes that the broad understanding of freedoms of press and speech was the dominant context of the First Amendment and of Fox's Libel Act, and that it enjoyed greater historical support.""--
The devising of narrow liberties of press and speech -- Blackstone's and Mansfield's narrow liberties of press and speech, and broad crimes of seditious libel and seditious words : summaries or misdescriptions of ancient common law? -- The crimes of seditious libel and seditious speech : political weapons for suppressing dissent in Britain and America? -- The emerging broad British view of freedoms of press and speech, before the colonial crisis -- The prevailing British view of freedoms of press and speech, in the decade before the American Revolution and declarations of rights -- The dominant British view of freedoms of press and speech, in the decade before Fox's Libel Act and America's Bill of Rights -- The emergence of expansive American views of freedoms of press and speech, before the colonial crisis -- Reasons for the spread of broad views of freedoms of press and speech in America, during and after the colonial crisis -- The prevailing broad view by the popular party of freedoms of press and speech, in the pre-Revolutionary decade before the American states' declaration of rights -- The dominant American view of freedoms of press and speech, in the decade leading up to ratification of the federal Bill of Rights -- The constitutional understanding of freedoms of press and speech, and of seditious libel, in discussions of state and federal Bills of Rights.
Includes bibliographical references and index.
Keywords: Blackstone, William -- 1723-1780.; Mansfield, William Murray -- Earl of -- 1705-1793.; United States; Freedom of expression -- Electronic books -- Great Britain; Freedom of expression -- United States; Freedom of speech -- Great Britain; Freedom of speech -- United States; Freedom of the press -- Great Britain; Freedom of the press -- United States